POTENSI WILAYAH DALAM PENGEMBANGAN KAWASAN AGROPOLITAN DI KABUPATEN TOBA SAMOSIR - Damiana Simanjuntak; Sirojuzilam Sirojuzilam (Ekonomi dan Keuangan, 2013)
ABSTRACT This research aims to analyze region  potency of Toba Samosir Regency in development of agropolitan region and formulate strategy of agropolitan region development in Toba Samosir Regency. This research uses secondary data in time series, that is GDP at current prices of Toba Samosir Regency and Sumatera Utara Province in 2003-2010. It is analyzed by Location Quotient (LQ) method dan Shift share analysis.  Strategy of agropolitan development is analyzed by quantitative SWOT analysis.The results of both analysis, Location Quotient (LQ) and shift share analysis show that sectors which are prime sector with their criteria clasified to fast growing, basis and competitive sectors are agricultural and industrial sector. Based on the result of SWOT analysis, strategy of agropolitan region development is developing those potential sectors, namely agricultural and industrial sectors. It can be conducted by increasing facilities and infrastructures, capital and agricultural education, making relationship with private sector in investment, utilizing agricultural land optimally by development of agricultural commodities and developing agricultural potency by resources utilization. Keywords: Region Potency, Agropolitan Region, Location Quotient (LQ), shift share, strategy.